(untitled) (Fiep Bulletin - online, 2019)
Objective: To analyze the national scientific production on the Family Health Strategy. Methodology: After applying thecriteria of inclusion and in-depth reading of the articles in the total of thirty-two productions, thirteen articles were selected to beanalyzed and demonstrated in three categories. Results: The main ideas of the articles about the host approach in the ESF arepresented in three categories: Reception from the Access point of view; Reception as solving, Access and organization of thesystem and Permanent Education. The subject is still little discussed in the scientific productions, especially with regard tointegrality in the ESF, the most frequent discussions deal with the reception only as access proper and little is said in theresolutiveness. Final Considerations: After completing the present study, we can consider that health care has expanded, butthere is still a need to subsidize permanent education actions for FHT teams, reception beyond nursing, specialization coursesand residency in Health of the Family, optimizing new approaches to the health-disease process.